An Analysis of Student Responses to The Implementation of Gamification at SMPN 2 Mojokerto - Kusuma, Wahyu Dewi; Hanafi, Muhammad; Astutik, Yuni Muji (ICONELT, 2024)
Gamification as a learning approach or strategy gains extensive attention among educators because it increases student engagement, motivation, and learning experiences. It is the integration and addition of game-like elements into the learning process. This research investigates the impact of implementing gamification on student responses at SMPN 2 Mojokerto, Indonesia. Implementing gamification in education aims to enhance students’ motivation to learn. Building on results from existing research, this study explores more detailed results of how learning outcomes are affected. The researchers of the qualitative studies interview and use questionnaires to comprehend the perceptions, attitudes, and academic performance of students. In this context, interviews and surveys are tools that qualitative studies researchers use in order to determine the views, attitudes, and academic achievement of the students. The results showed that gamification made learning an enjoyable challenge and increased the motivational and active participation of students in class by a remarkable percentage. Students like storytelling and frank criticism; it increases comprehension and memory. It improved academic achievements, especially in those challenging fields of languages. However, several challenges were pointed out, including competitive pressure and technical problems. The results identify the importance of a rich gamification strategy and auxiliary technical support. All things being equal, this study points toward a number of advantages that gamification offers as a pedagogical practice while pointing out the urgent need to address issues with its sustained use in the classroom.